Religious And Cultural Tourism Objects In Sigando Village: A Perspective Of Power Relations And Conflict Theory - H, Afrizal; Rahmatika, Aulia (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
This study aims a title “Objek Wisata Religi dan Budaya Kelurahan Sigando: Perspektif Relasi Kuasa dan Teori Konflik” to investigate the power relations and various conflicts that arise from the determination of Sigando Village as a Cultural and Religious Village. This determination often involves various parties, such as local government, local communities, and other stakeholders. Through a power analysis approach, this study will explore the dynamics of power that underlie the determination process, including the interaction between the government and local communities, and its implications for the identity and sustainability of local culture. The study uses a qualitative approach with case studies, this study will analyze the dynamics of interactions between various related parties, including local government, local communities, and tourism actors. Observation, interview, and document analysis methods will be used to collect relevant data. This study is expected to provide a better understanding of the complexity of power relations in the context of determining tourism and cultural destinations at the local level. The findings of this study are expected to provide a deeper understanding of how power is reproduced and maintained in the context of determining tourism and cultural destinations, as well as its implications for the development and empowerment of local communities.